The imbalance of biliary microflora in hepatolithiasis. (August 2021) - Xiao, ZhouQing; Huang, ZhiHao; Gao, Jun; Wang, JiaKun; Lei, Jun; Zhou, Fan; Yin, XiangBao; Liao, WenJun; Wu, LinQuan
Abstract: Background: The imbalance of microbial flora is thought to be associated with many diseases. However, the characteristics of the biliary microflora and its relation to in hepatolithiasis are unknown. Methods: This study included 40 patients with hepatolithiasis and 10 control patients. Bile samples were taken during hepatectomy surgeries and 16S rRNA sequencing was performed. The sequencing results were analyzed by operational taxonomic unit (OTU) clustering, species annotation and abundance analyses, sample complexity analyses, diversity analyses, and environmental factor correlation analyses. Results: There were significant differences in bile microflora between the hepatolithiasis group and the control group. We found that the abundance of microflora in the bile of patients with hepatolithiasis was relatively high (52.4% versus 40.2% and 42.1% versus 29.6%). The diversity of microflora in the bile of patients with hepatolithiasis decreased significantly (Shannon (P = 0.004), Observed species (P = 0.001), PD-whole-tree (P = 0.001)). These differences are mainly associated with Enterococcus (P＜0.001), Enterobacter (P = 0.003). In addition, we found that there were intra-group differences in hepatolithiasis, but the differences in the hepatolithiasis group were generally smaller than the differences in the non-hepatolithiasis group. Conclusion: There is an imbalance of microflora in the bile duct of patients with hepatolithiasis. The imbalance of biliary flora may be associated with hepatolithiasis pathogenesis. Highlights: Analysis of the characteristics of bile flora in patients with hepatolithiasis by high-throughput sequencing. We found the imbalance of bile duct microflora in patients with hepatolithiasis. The occurrence of hepatolithiasis is related to biliary tract infection.